2021
DOI: 10.1021/acs.orglett.1c03279
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric [4 + 3] Annulations for Constructing Divergent Oxepane Frameworks via Cooperative Tertiary Amine/Transition Metal Catalysis

Abstract: We report asymmetric [4 + 3] annulations between isatin-derived Morita–Baylis–Hillman carbonates and two types of vinyl carbonates synergistically catalyzed by tertiary amines and transition metals, through chemoselective assemblies of in situ formed allylic ylides and metal-containing 1,4-dipoles. A range of oxepane frameworks are generally constructed in moderate to good yields with high stereocontrol. Moreover, all four diastereomers for the products bearing vicinal stereocenters are accessible by tuning te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…In addition, the MBH carbonates from isatins are allylic alcohol derivatives, which are inherently and possibly converted to π-allylmetal species under palladium or iridium catalysis; nevertheless, our recent work demonstrated that they would not be affected by transition metals in the presence of simple allylic carbonates, thus enabling successful cooperative activations of Lewis base and transition metal catalysts (Scheme b) . Although similar phenomena were further observed between the isatin-derived MBH carbonates and other allylic derivatives, here we disclosed that the corresponding π-allylpalladium intermediate III indeed could be generated from the MBH carbonate 1a under Pd(0) catalysis in the absence of other allylic derivatives, rendering the regioselective Tsuji–Trost allylation with suitable nucleophiles, such as o -hydroxybenzylideneacetone 2a . More importantly, the resultant O -allylation intermediate 3a with multiple functionalities could undertake a cascade reaction process under relay Brønsted base catalysis, straightforwardly delivering the complex 1,2,3,4-tetrahydrodibenzo­[ b , d ]­furan architecture 4a incorporating another oxindole pharmacophore motif.…”
supporting
confidence: 64%
“…In addition, the MBH carbonates from isatins are allylic alcohol derivatives, which are inherently and possibly converted to π-allylmetal species under palladium or iridium catalysis; nevertheless, our recent work demonstrated that they would not be affected by transition metals in the presence of simple allylic carbonates, thus enabling successful cooperative activations of Lewis base and transition metal catalysts (Scheme b) . Although similar phenomena were further observed between the isatin-derived MBH carbonates and other allylic derivatives, here we disclosed that the corresponding π-allylpalladium intermediate III indeed could be generated from the MBH carbonate 1a under Pd(0) catalysis in the absence of other allylic derivatives, rendering the regioselective Tsuji–Trost allylation with suitable nucleophiles, such as o -hydroxybenzylideneacetone 2a . More importantly, the resultant O -allylation intermediate 3a with multiple functionalities could undertake a cascade reaction process under relay Brønsted base catalysis, straightforwardly delivering the complex 1,2,3,4-tetrahydrodibenzo­[ b , d ]­furan architecture 4a incorporating another oxindole pharmacophore motif.…”
supporting
confidence: 64%
“…On the basis of our experimental observation and the related literature studies, ,, a plausible mechanism was proposed to illustrate the catalytic cycle (Scheme ). Coordination of a palladium(0) catalyst to 2-alkylidenetrimethylene carbonates 2 or (2-(hydroxymethyl)-3-arylallyl) carbonates 6 gives π-allylpalladium intermediates A-2 or A-6 .…”
Section: Resultsmentioning
confidence: 78%
“…However, in this aspect, the vast majority of the transformations are confined to the [3 + 2] cycloaddition with diverse π-allyl palladium 1,3-dipoles for the generation of indoline-fused five-membered ring compounds (Scheme a). In addition, there are only two examples of the [4 + 2] cycloaddition with π-allyl palladium 1,4-[ N , C ]-dipoles for the construction of indoline-fused tetrahydroquinolines via palladium-catalyzed decarboxylation of vinyl benzoxazinanones (Scheme b) . On the other hand, 2-alkylidenetrimethylene carbonates have proved to be a type of π-allyl palladium 1,4-[ O , C ]-dipole precursors, which were used in diverse palladium-catalyzed decarboxylative cycloaddition reactions . However, to the best of our knowledge, the possible involvement of π-allyl palladium 1,4-[ O , C ]-dipoles in the dearomative cycloaddition of electron-deficient heteroarenes has not been exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Chen and Du proved the generality of a cooperative catalytic strategy in reactions of HODAs with vinyl carbonates (Scheme 16). 52 In the presence of a chiral Pd catalyst and DABCO, vinyl carbonate 74 smoothly reacted with oxindole-derived carbonates 75 to afford spiro-cycloether product 76 in high yields and good enantiocontrols. In the presence of a chiral Ir catalyst and pyridine catalyst, similar medium-sized cyclic products were synthesized from vinyl carbonates 77 and oxindole-derived carbonates 75 .…”
Section: π-Allyl-m-type Mcrdsmentioning
confidence: 99%